Retrospective review on patients admitted for violent crime in Permai Hospital, Malaysia. - Md Rosli, Najwa Hanim; AB, Abdul Kadir (Malaysian Psychiatry Association, 2011)
Objective: To study the demographic data of patients and the pattern of crime in the study group, to look at the outcome of assessment by psychiatrist on fitness to plea and insanity at time of offense and to assess association between the nature of crime with presence of psychopathology during the crime. Methods: This is a retrospective study. All available case notes for 342 forensic admissions from January 2007 until March 2010 were reviewed. All related information on 135 patients that committed violent crime was taken for analysis. Results: Majority of patients were male, Malay, single, education up to secondary school and unemployed. Only 38% of patients had encountered psychiatric services, 20% had previous imprisonment and 49% had history of substance usage. In cases involving victims (87%), 64% the victims were known to the patient, 53% had hallucination or delusion or both at the time of crime and 90% was found to have some diagnosis of mental illness after psychiatrist assessment. Only 81% of formal forensic reports were available in the case note and it showed 94% were fit to plea and 82% were at sound mind at the time of offense. Conclusion: Substance abuse had high prevalence among the patient. Almost 2/3 never had any encounter with psychiatric services before the admission. Even with the high percentage of patient diagnosed with mental illness, they were still found to be fit to plea in court and are at sound mind at the time of offense.